2019
DOI: 10.3389/fenrg.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Overtopping Breakwater for Energy Conversion (OBREC) Systems Using the Harmony Search Algorithm

Abstract: The European Union, in its Framework Strategy for A Resilient Energy Union, as described in the "Clean Energy for all Europeans" package of measures, marked its energy priorities for transition to a low-carbon, secure and competitive economy. Following this direction, the paper deals with the exploitation of one of the most significant and extensively available energy sources, that of nearshore waves. More specifically the paper emphasizes in the optimal design of Overtopping Breakwater for Energy Conversion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The overall average performance of OBREC was about 6.62 kW for cubic shape and 4.81 kW for linear shape. On the other hand, the result presented in this section is quite similar to the finding calculated by (Kralli et al, 2019;Palma et al, 2020) who estimated OBREC power contribution in deference places and situations. The percentage of wave energy captured by the device could be defined as hydraulic efficiency, shown in Table 4.…”
Section: Cubic Rampsupporting
confidence: 91%
“…The overall average performance of OBREC was about 6.62 kW for cubic shape and 4.81 kW for linear shape. On the other hand, the result presented in this section is quite similar to the finding calculated by (Kralli et al, 2019;Palma et al, 2020) who estimated OBREC power contribution in deference places and situations. The percentage of wave energy captured by the device could be defined as hydraulic efficiency, shown in Table 4.…”
Section: Cubic Rampsupporting
confidence: 91%
“…However, there is no adequate data to estimate the extra energy that can be generated by the swells. Experimental tests performed by Kralli et al [24] indicated that an OBREC can achieve a performance that is improved by 20% due to the incidence of swell waves.…”
Section: Ocean Wave Energy and Its Conversionmentioning
confidence: 99%
“…Then the iteration continues until the predetermined maximum number of iterations (NIs) is reached. Moreover, harmony search algorithms and their variants have been developed and successfully applied to address practical problems [34][35][36]. Channel selection based on the binary harmony search method was proposed to optimize the channels and enhance the BCI system accuracy [29].…”
Section: Introductionmentioning
confidence: 99%